ELECTRICAL PROPERTIES OF CAMBRIAN ROCKS IN VOLYNO-PODILLIA - Vyzhva, S.; Onyshchuk, D.; Onyshchuk, V.; Pastushenko, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this article, we present the results of applying a petroelectrical research technique to complex terrigenous and carbonate reservoirs. There have been determined the petroelectrical properties and their relation to porosity and permeability of sandstones, dolomites and limestones (Cambrian deposits) from the Volodymyrska area, Volyno-Podillia. The aim of the research was to build petroelectrical models of reservoir rocks to ensure a comprehensive analysis of electrical parameters of rocks and their correlation with porosity and permeability. Determining effective resistivity of reservoir rocks can provide data on: changes in different types and groups of rocks, stratigraphic horizons, facies and geological sections; correlations between effective resistivity and mineral composition, pore structure, substance phase ratio, electric field intensity and frequency; resistance variations due to epigenetic transformation and metamorphic changes in rocks. Petrophysical laboratory studies included determining: bulk density of rocks (both dry and saturated with synthetic brine); effective porosity (obtained by nitration and synthetic brine saturation); residual water saturation factor (by centrifugation); permeability (by stationary nitrogen filtration method); interval time (P-wave velocity) and electrical resistivity. Laboratory research yielded data on the petroelectrical parameters of Cambrian sandstones, dolomites and limestones from the hydrocarbon prospective Volodymyrska area, as well as empirical correlations between petroelectrical parameters, porosity and permeability of the studied rocks. It has been found that the electrical resistivity of the dry extracted samples (mainly determined by electrical resistance of the rock matrix) ranges from 5,2·104 Ohms m (sandstones) to 2,4·107 (dolomites), with an average value of 3,8·106. The electrical resistivity of synthetic brine saturated rock samples (NaCl solution) ranges from 7,2 Ohms m (sandstones) to 73 (limestones), with an average value of 45. The formation resistivity factor ranges from 20,4 to 85,5, with an average value of 44,1 (sandstones); from 143,9 to 207,6, with an average value of 188,6 (limestones); from 81,7 to 198,7, with an average value of 155.6 (dolomites). The variation range of the resistance increase is: from 1 to 3,24, with an average value of 1,24 (sandstones); from 1 to 7,19, with an average value of 2,24 (limestones); from 1 to 2,76, with an average value of 1,44 (dolomites). Sandstones are characterized by changes in resistance from 1 to 2,12, with an increase in pressure from atmospheric to hydrostatic (to 59 MPa), while for limestones the resistivity index ranges from 1 to 7,7, with pressure ranging between 0-49 MPa. There have been found correlations between electrical resistivity and porosity ratio, as well as resistance increase and the water saturation ratio in the laboratory and reservoir conditions, which may be used as a framework for geological interpretation of geophysical data. These correlation dependences are generally approximated by the power function. Data analysis shows that petroelectrometric studies are a powerful tool in laboratory and field research, being efficient enough to give extensive and useful information about rock properties. Laboratory data on electrical resistance of rocks may be employed to further reinforce the interpretation of the results of electrometric well logging and electric exploration.
Keywords: core; water saturation; fluid; borehole; Cambrian; sandstone; limestone; dolomite; centrifuge; porosity; electrical resistivity; pressure; permeability; petroelectrical parameters; correlation dependence